2003
DOI: 10.1074/jbc.m302818200
|View full text |Cite
|
Sign up to set email alerts
|

Protein 14-3-3σ Interacts with and Favors Cytoplasmic Subcellular Localization of the Glucocorticoid Receptor, Acting as a Negative Regulator of the Glucocorticoid Signaling Pathway

Abstract: The glucocorticoid receptor (GR) ␣ interacts with the highly conserved 14-3-3 family proteins. The latter bind phosphorylated serine/threonine residues of "partner" molecules and influence many signal transduction events by altering their subcellular localization and/or protecting them from proteolysis. To examine the physiologic role of 14-3-3 on the glucocorticoid-signaling pathway, we studied the nucleocytoplasmic shuttling and transactivation properties of GR␣ in a cell line replete with or devoid of 14-3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 40 publications
2
42
2
Order By: Relevance
“…Pratt and colleagues have demonstrated that components of the apoGR complex bind cytoskeletal factors (Galigniana et al, 2001). Alternatively, Kino et al (2003) have suggested that binding to the 14-3-3 protein helps tether apoGR to the cytoplasmic compartment. Given these observations, it would be interesting to examine the intracellular distribution of GR in the absence of hormone by electron microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Pratt and colleagues have demonstrated that components of the apoGR complex bind cytoskeletal factors (Galigniana et al, 2001). Alternatively, Kino et al (2003) have suggested that binding to the 14-3-3 protein helps tether apoGR to the cytoplasmic compartment. Given these observations, it would be interesting to examine the intracellular distribution of GR in the absence of hormone by electron microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…It seems plausible that cdc42 isoform1, a RhoGTPase family member with a polybasic region in its C-terminal end that can function as a nuclear localization signal (Lanning et al 2003, Williams 2003, might perform this function since we identified both isoforms 1 and 2 of cdc42 in our agarose gel purification experiments as ERa-associated proteins (Schultz-Norton et al 2007). Alternatively, RhoGDIa could be accompanied by a protein such as 14-3-3, which binds and helps to redistribute an array of signaling proteins (Fu et al 2000, Kino et al 2003, Diviani et al 2004. It should also be noted that the 28 kDa RhoGDIa is theoretically small enough to traverse the nuclear pores unaccompanied.…”
Section: Discussionmentioning
confidence: 99%
“…The GFP-fused 14-3-3s plasmid (Kino et al, 2003) was kindly provided by Dr T Kino (NIH, Bethesda, MD, USA). Transient transfection was performed using lipofectin (Life Technologies, Rockville, MD, USA), according to the manufacturer's protocol.…”
Section: Detection Of Subcellular Localization Of Gfp-fused 14-3-3smentioning
confidence: 99%